On split null point and common fixed point problems for multivalued demicontractive mappings. (3rd June 2021) - Wang, Yaqin; Fang, Xiaoli; Guan, Jin-Lin; Kim, Tae-Hwa
ABSTRACT: In this paper, we introduce a new viscosity iterative method for solving the split null point and common fixed point problems for maximal monotone operators and multivalued demicontractive mappings in Hilbert spaces, and we obtain some strong convergence results under some suitable assumptions. As applications, we apply our results to the split feasibility problem and the split minimization problem. The results obtained in this paper generalize and improve the recent ones announced by many authors.